2023
DOI: 10.1002/2211-5463.13566
|View full text |Cite
|
Sign up to set email alerts
|

The NLRP3 inflammasome – interleukin 1β axis in uveal melanoma

Abstract: Uveal melanoma (UM) is the most common primary intraocular cancer in the adult population. Recent studies suggested that the NLRP3 inflammasome could be a therapeutic target for cutaneous melanoma (CM), but the role of NLRP3 in UM remains unknown. Here, we analyzed the NLRP3‐IL‐1β axis in 5 UM and 4 CM cell lines. Expression of NLRP3 mRNA in UM and CM was low, and expression in UM was lower than in CM (P < 0.001). NLRP3 protein levels were below detection limit for all cell lines. UM exhibited lower baseline I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…NLRP3 (NLR family, pyrin domain-containing 3) has become an important target for cancer treatment, especially in melanoma cancer. Some studies have found that NLRP3 inflammasome may be a therapeutic target for cutaneous melanoma (CM) and uveal melanoma (UM) [ 20 ]. NLRP3 is involved in the regulation of inflammatory response and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…NLRP3 (NLR family, pyrin domain-containing 3) has become an important target for cancer treatment, especially in melanoma cancer. Some studies have found that NLRP3 inflammasome may be a therapeutic target for cutaneous melanoma (CM) and uveal melanoma (UM) [ 20 ]. NLRP3 is involved in the regulation of inflammatory response and apoptosis.…”
Section: Discussionmentioning
confidence: 99%